Noise-induced Hearing Loss and Its Determinants among Workers at Vachira Phuket Hospital - Kamchuchat, Chalermrat (Journal of Health Science of Thailand, 2018)
This descriptive study was aimed at investigating 3 difference courses: 1) the occupational noise exposure level, 2) the prevalence of noise - induced hearing loss (NIHL), and 3) the factor of noise-induce hearing loss (NIHL). This study was designed by using a cross - sectional study with analytic components. The observation groups included 53 workers from 2 departments in Vachira Phuket Hospital (sewing and laundry service department, and culinary service department) during April - June 2007. A walk - through survey and noise level assessment were conducted by using a sound level meter, history - taking, evaluation and audiometry test. Finally, the data were analyzed employing chi-square, odds ratio and 95% confidence interval. The result showed that, occupational noise exposure levels were 78.1 decibel A-dB (A) in the sewing and laundry service department and 74.7 dB(A) in the culinary service department. The number of workers, who had their hearing assessed, was 39 from the total of 53 people or 73.6 percent. It was found that the prevalence of NIHL was 51.3 percent on average. The prevalence of NIHL in the sewing and laundry service department was 47.6 percent and in the culinary service department was 55.6 percent. The observation groups were consisted of 79.5 percent of female aged over 42.4 years and exposed to noise 4 - 8 hours a day for 12.6 years (56.4%). The survey showed that 64.1 percent of workers had not used personal protective eguipment (PPE) while working, meanwhile 60.0 percent cited unavailability of PPE and 54.5 percent referred to inconveniences. No correlation between hearing loss and factors included in the study-smoking behavior, sex, age, working duration and working place. In conclusion, the NIHL is an occupational problem among workers in Vachira Phuket hospital and the hearing loss prevention programs should be urgently established.